Effect of adapted dance program on gait in adults with cerebral palsy: a pilot study - Hee Joung Joung; Tae Hoon Kim; Moon Seok Park; Moon Seok Park (Frontiers in Neurology, 2024)
BackgroundThe gait function in adults with cerebral palsy (CP) deteriorates rapidly with age. Dance has been used as an effective intervention to improve balance, postural control, and gait. This study aimed to investigate the feasibility and effects of an adapted dance program (ADP) on the gait in adults with CP. The ADP, which consists of floor and barre workouts, was designed to be adapted for individuals with CP.MethodTen female adults with spastic diplegic CP (mean age 52.3 ± 6.34, Gross Motor Function Classification System level II) participated in this study. Outcome measures, examined using 3D gait analysis, included spatiotemporal gait parameters and the Gait Deviation Index (GDI) based on nine kinematic variables in all planes of motion. To assess feasibility, we conducted post-questionnaires and a group interview. The ADP, each lasting 90 min, was held twice per week for 12 weeks.ResultsA statistically significant improvement was observed in GDI (Δ5.74 points, p = 0.014), with a large effect size (d = 0.76). Foot off (Δ-0.72%), first double support (Δ-0.2%), second double support (Δ1.5%), and single support (Δ0.64%) showed no significant differences. Step length (Δ1.48 cm), cadence (Δ3.95 steps/min), and walking speed (Δ6.41 cm/s) tended to increase, though the differences were not statistically significant. Participants expressed high levels of physical and emotional satisfaction, suggesting a need for early intervention.ConclusionThe ADP may improve gait patterns in adults with spastic diplegic CP. The feasibility results indicated that the ADP is suitable for adults with spastic diplegic CP. This study provides evidence for improvement in gait patterns through dance, which has not been reported in previous dance studies on individuals with CP, offering additional information on the benefits of dance.